Management of Changes in Socio-Economic Systems - Endovitsky, Dmitry A.; Popkova, Elena G. (Studies in Systems, Decision and Control, 2018)
This book addresses changes in socio-economic systems. To do so, it employs the evolutional approach, which views changes in socio-economic systems from an evolutionary standpoint connecting the past, present and future, and focuses on preventing sudden, high-risk changes. The changes in socio-economic systems are also studied with the help of the system approach, which calls for assessing complex economic subjects, characterized by the sustainable connections between their elements, as socio-economic systems.  Combining these two approaches in the context of studying the changes in socio-economic systems is unprecedented in modern economic science. The book studies various issues that cover both fundamental aspects of the system organization of economy and management and applied aspects of managing changes in socio-economic systems.  The target audience of the book includes scholars and experts whose work involves studying the dynamic process of modern socio-economic systems' development. The scientific conclusions and practical recommendations that the book provides can be applied to the development and implementation of state economic policy in various countries around the world.